E-Learning and Blended Learning in the Opinions of Polish Students - Marzena Chrost; Sławomir Chrost (Ignatianum University Press, 2021)
For the first time in history, the education system has experienced a crisis situation on a global scale, leading to total and forced isolation in social life and communication. In March 2020, full-time classes at universities in Poland were suspended due to the epidemic caused by the COVID-19 coronavirus. This state of affairs resulted in the need to shift scientific and didactic work to be "remote". This article aims to present students' opinions on e-learning and blended learning after several months of experience with such forms of learning. The main research problem was formulated as follows: "What are the Polish students' opinions of e-learning during the pandemic?" The method of diagnostic survey and the questionnaire technique called the SWOT were used in the empirical research. The research was conducted in May and June 2020 in three selected universities. A total of 314 students took part in it. The results indicate that remote teaching has both specific strengths and weaknesses and that there are many opportunities and threats associated with this form of teaching; nevertheless, a larger proportion of the data were related to the weaknesses. Undoubtedly, there are still many activities that should be introduced into practice and everyday academic education. Perhaps a creative solution will be to introduce only some elements of distance learning, which can contribute to a better acquisition of IT and digital competences and can help students develop activity, self-discipline, and independent learning.